Intake of macronutrients and micronutrients in adolescents - Díaz Wever, Nayka (2021)
The eating patterns of adolescents are influenced by internal and external factors, such as food preferences, perception of body weight and influence of the environment, parents and friends. The consumption of macro and micronutrients was evaluated in 130 adolescents aged 14 to 17 years, of both sexes. It was a non-experimental, cross-sectional, exploratory and comparative study. Three 24-hour reminders were used (two working days and one weekend day). The composition of energy, macronutrients (proteins, fats, carbohydrates, fibers and cholesterol) and micronutrients was calculated and the adequacy of these nutrients (115% was considered deficient intake) (RDA) was determined. Student's t, ANOVA was used to compare variables by sex and age. Men showed higher average values ​​of energy, protein, carbohydrates, fat, cholesterol, saturated, monounsaturated and polyunsaturated fat consumption at all ages. 60.8% and 40% showed inadequate energy and protein; as well as, vitamin E and folic acid (more than 90%). The adolescents in this sample had a low consumption of fruits and vegetables, constituting a vulnerable group to chronic non-communicable diseases related to nutrition.